Interaction of k-carrageenan with sodium carboxymethyl cellulose derived from nata biocellulose - Pidlaoan, Victorio P.
Cellulos derived from nata has the advantage of being free from impurities such as hemicelluloses and lignins. Sodium carboxymethyl cellulose is the most widely used of all gums. In this study, sodium carboxymethyl cellulose was produced using nata de coco as the raw material. the nata CMC produced was off-white to cream color. Degree of substitution values ranged from 0.8 to 1.1. The solutions had apparent viscosities of 108 to 133 cps. The product showed significant interaction with κ-carrageenan in terms of viscosity. The total viscosity of the mixed solution was twice that of the individual components combined. In terms of gel strength, the gel was weaker than observed with pure κ-carrageenan. The decrease in gel strength was directly related to the nata CMC concentration. The gel melting temperature and gelling temperature were not significantly altered.